Forward electrohydrodynamic inkjet printing of optical microlenses on microfluidic devices. Issue 2 (11th December 2015) - Vespini, V.; Coppola, S.; Todino, M.; Paturzo, M.; Bianco, V.; Grilli, S.; Ferraro, P.
Abstract : We report a novel method for direct ink-jet printing of viscous polymers based on a pyro-electrohydrodynamic repulsion system capable of overcoming limitations of previous classical EHD ink-jet printing on the material type, geometry and thickness of the receiving substrate. Abstract : We report a novel method for direct printing of viscous polymers based on a pyro-electrohydrodynamic repulsion system capable of overcoming limitations on the material type, geometry and thickness of the receiving substrate. In fact, the results demonstrate that high viscosity polymers can be easily manipulated for optical functionalizing of lab-on-a-chip devices through demonstration of direct printing of polymer microlenses onto microfluidic chips and optical fibre terminations. The present system has great potential for applications from biomolecules to nano-electronics. Moreover, in order to prove the effectiveness of the system, the optical performance of such microlenses has been characterized by testing their imaging capabilities when the fibroblast cells were allowed to flow inside the microfluidic channel, showing one of their possible applications on-board a LoC platform.